Concordance of Attachment Representations in Mother-/Father-Child Dyads and between Siblings - Marie Stievenart; Isabelle Roskam (Psychologica Belgica, 2013)
This study focuses on the concordance of attachment representations in two-parent, two-child families as an original contribution to the current attachment literature. It uses both categorical attachment patterns and continuous scores. Data was collected on 92 native French-speaking Belgian families. In order to disentangle conceptual and methodological interpretations, each hypothesis was tested in two complementary ways: first in a sample where the parent completed the 'Cartes pour les Modèles Internes de Relation' (CaMir) and their young children (four- to seven-year-olds) the French version of the 'Attachment Story Completion Task'(Fr-ASCT) and second, in a sample where both parents and their teenage to young-adult children (15- to 34-year-olds) completed the CaMir. Our results indicated very little if any concordance of attachment representations, either when using categorical scores or when using continuous scores. The implications of these results for both theoretical and research purposes are discussed.